Founder mutation in the PMM2 promotor causes hyperinsulinemic hypoglycaemia/polycystic kidney disease (HIPKD). Issue 12 (3rd April 2021) - Islam, Sumaya; Tekman, Mehmet; Flanagan, Sarah E.; Guay‐Woodford, Lisa; Hussain, Khalid; Ellard, Sian; Kleta, Robert; Bockenhauer, Detlef; Stanescu, Horia; Iancu, Daniela
Abstract: Background: Polycystic kidney disease with hyperinsulinaemic hypoglycaemia (HIPKD) is a recently described disease caused by a single nucleotide variant, c.‐167G>T, in the promoter region of PMM2 (encoding phosphomannomutase 2), either in homozygosity or compound heterozygosity with a pathogenic coding variant in trans . All patients identified so far are of European descent, suggesting a possible founder effect. Methods: We generated high density genotyping data from 11 patients from seven unrelated families, and used this information to identify a common haplotype that included the promoter variant. We estimated the age of the promoter mutation with DMLE + software, using demographic parameters corresponding to the European population. Results: All patients shared a 0.312 Mb haplotype which was absent in 503 European controls available in the 1000 Genomes Project. The age of this mutation was estimated as 105–110 generations, indicating its occurrence around 600 BC, a time of intense migration, which might explain the presence of the same mutations in Europeans around the globe. Conclusion: The shared unique haplotype among seemingly unrelated patients is consistent with a founder effect in Europeans. Abstract : We identified a founder effect for the specific promoter variant that causes polycystic kidney disease and Hyperinsulinsim (HIPKD). The variant arose approximately 2500 years ago in Central Europe.